1997
DOI: 10.1111/j.1365-2621.1997.tb03994.x
|View full text |Cite
|
Sign up to set email alerts
|

Heat‐Induced Gelation Properties of Surimi From Mechanically Separated Chicken

Abstract: Chicken surimi was prepared from fresh mechanically separated chicken meat using a sodium bicarbonate washing process. The heat-induced gelation properties were assessed under different conditions of pH, temperature, heating rate, protein and sodium tripolyphosphate (TPP) concentrations. Surimi gel strength increased (p Ͻ 0.05) after: reducing pH from 6.4 to 6.0, increasing temperature from 40ЊC to 80ЊC, reducing heating rate from 5ЊC/min to 1ЊC/min, increasing protein concentration from 4% (w/w) to 8% (w/w) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
41
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 36 publications
5
41
0
Order By: Relevance
“…The results of the proximate composition of the MSCM obtained in this study were compared with data previously reported by other authors (Grunden et al 1972;Essary 1979;Froning 1981;Mott et al 1982;Hamm and Young 1983;Smyth and O'Neill 1997;Rivera et al 2000;Perlo et al 2006).…”
Section: Compositional Properties Of Mscm and Mscm Surimi-like Materialssupporting
confidence: 59%
See 4 more Smart Citations
“…The results of the proximate composition of the MSCM obtained in this study were compared with data previously reported by other authors (Grunden et al 1972;Essary 1979;Froning 1981;Mott et al 1982;Hamm and Young 1983;Smyth and O'Neill 1997;Rivera et al 2000;Perlo et al 2006).…”
Section: Compositional Properties Of Mscm and Mscm Surimi-like Materialssupporting
confidence: 59%
“…Yield % = (whole muscle weight−surimi-like material weight)/(whole muscle weight)−100 (Jin et al 2007). pH pH was measured in triplicate using a digital pH meter (Marconi model PA 200, Piracicaba, Brazil) About 10 g of sample (MSCM or MSCM surimi-like material) was cut into small pieces to which 50 ml of distilled water was added and slurry was made using a blender and the pH was recorded (Smyth and O'Neill 1997).…”
Section: Yieldmentioning
confidence: 99%
See 3 more Smart Citations